2014
DOI: 10.1155/2014/152659
|View full text |Cite
|
Sign up to set email alerts
|

Chlorotoxin-Fc Fusion Inhibits Release of MMP-2 from Pancreatic Cancer Cells

Abstract: Chlorotoxin (CTX) is a 36-amino acid peptide derived from Leiurus quinquestriatus (scorpion) venom, which inhibits low-conductance chloride channels in colonic epithelial cells. It has been reported that CTX also binds to matrix metalloproteinase-2 (MMP-2), membrane type-1 MMP, and tissue inhibitor of metalloproteinase-2, as well as CLC-3 chloride ion channels and other proteins. Pancreatic cancer cells require the activation of MMP-2 during invasion and migration. In this study, the fusion protein was generat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
19
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 48 publications
(62 reference statements)
5
19
0
Order By: Relevance
“…6I and S6H). Similar pattern of CLTX's association with GBM cells was also suggested by previous studies using CLTX-coated nanoparticles and fusion proteins (57,83). Of note, correlation was observed between MMP2 expression, degranulation ( Fig.…”
Section: Discussionsupporting
confidence: 86%
“…6I and S6H). Similar pattern of CLTX's association with GBM cells was also suggested by previous studies using CLTX-coated nanoparticles and fusion proteins (57,83). Of note, correlation was observed between MMP2 expression, degranulation ( Fig.…”
Section: Discussionsupporting
confidence: 86%
“…More recently it was shown that ClTx-modified liposomes are capable of significantly inhibit breast tumor 4T1 growth, an aggressive metastatic breast cancer cell line derived from a BALB/c mouse mammary tumor, which highly expresses MMP-2, as well as increasing the antimetastasis effect (Qin et al, 2014). A different vehicle, a nanocapsule exhibiting the monomeric fusion of chlorotoxin to the amino terminus of the human IgG-Fc (M-ClTx-Fc), was internalized and inhibited the migration of pancreatic cancer cells (El-Ghlban et al, 2014). Many groups have been working in the elaboration of nanoparticles conjugated with chlorotoxin specific to glioma, either to access/treat this cancer or to monitor/visualize the tumor growth (a recent revision is presented in Fu et al (2012)).…”
Section: Anticancer Peptidesmentioning
confidence: 99%
“…A number of antibacterial, antifungal (yeast) and antiviral substances have been derived from peptides isolated from scorpion venom (13,14). Additionally, scorpion venom has demonstrated anticancer potential in pancreatic cancer (15) and leukemia (16). Scorpion venom is constituted by a complex mixture of salts, nucleotides, biogenic amines, peptides, enzymes, mucoproteins and other proteins such as neurotoxins (17).…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have demonstrated that a 36-amino acid peptide sequence, which contains four disulfide bridges and derives from scorpion venom, is effective in inhibiting the action of various MMPs in glioblastoma (29)(30)(31), pancreatic (15) and breast cancer (32). However, there are limited studies on the effect of scorpion venom as an anticancer agent on colorectal cancer.…”
Section: Introductionmentioning
confidence: 99%